Pemanfaatan Aplikasi Pendaftaran Online BPJS Pada Pasien Ibu Hamil Rawat Jalan - Parningotan Simanjuntak; Nopalina Suyanti Damanik (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Background: In the current digital era, with the increasingly rapid development of information technology in the health sector, patients can register using the P Care application using the patient's smartphone. It is hoped that this application can improve the minimum hospital service standards that have been set, so that it can overcome the problem of queuing for registration services. The aim of this community service program (PKM) is to increase the utilization of the BPJS online registration application for outpatient pregnant women at the Sei Bejangkar Community Health Center, Batubara Regency in 2023. The methods used include 1) identification of pregnant women at the Pematang Panjang Community Health Center); 2) preparation of materials and steps for the BPJS online registration application); 3) implementation of BPJS online registration application education for outpatient pregnant women). Results Based on the results of the implementation of service to outpatient pregnant women at the Sei Bejangkar Community Health Center, Batubara Regency, there are a total of 68 pregnant women as members, where the majority are aged 20-35 years, 58 pregnant women (85%), < 20 years old, 10 pregnant women (15% ), all participants were enthusiastic about educating on the BPJS online registration application. all participants were enthusiastic about using the BPJS online registration application on.